The Advances in Fluid Mechanics - Blanco, Jesús María (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint collects research papers on mathematical and numerical modelling in fluid dynamics, discusses latest research developments in areas of fluid flows heat and mass transfer, and focuses on special topics and applications of tech-related real-world applications.